Niels Viggo Bentzon (1919-2000): Symphony no. 8: Symphonic variations op. 92 - Bentzon, Niels Viggo; Bostock, Douglas (Denmark Classico, 2005)
Symphony No. 8, Op. 113 "Sinfonia Discrezione"1Allegro ma non troppoNiels Viggo BentzonDouglas Bostock17:252Allegro moltoNiels Viggo BentzonDouglas Bostock5:463Andante tranquilloNiels Viggo BentzonDouglas Bostock10:054AllegroNiels Viggo BentzonDouglas Bostock11:20Symphonic Variations, for orchestra, Op. 925Molto moderatoNiels Viggo BentzonDouglas Bostock3:396Variation 1 AllegroNiels Viggo BentzonDouglas Bostock1:567Variation 2 Poco menoNiels Viggo BentzonDouglas Bostock2:388Variation 3 AllegroNiels Viggo BentzonDouglas Bostock2:059Variation 4Niels Viggo BentzonDouglas Bostock1:0410Variation 5Niels Viggo BentzonDouglas Bostock1:2411Variation 6 Poco menoNiels Viggo BentzonDouglas Bostock1:1112Variation 7 Con motoNiels Viggo BentzonDouglas Bostock1:1513Variation 8Niels Viggo BentzonDouglas Bostock0:3414Variation 9Niels Viggo BentzonDouglas Bostock1:0215Variation 10 SostenutoNiels Viggo BentzonDouglas Bostock1:31